The effect of oral glucose supplements on muscle protein synthesis following resistance training - Roy, B. D.; Tamopolsky, M. A.; MacDougall, J. D.; Fowles, J.; Yarasheski, K. E. (Medicine & Science in Sports & Exercise, 1996)
The ingestion of a CHO supplement (1 gm/kg) immediately following completion of resistance training can significantly decrease myofibrillar protein breakdown and may slightly increase muscle protein synthetic rate resulting in a more positive protein balance. Implication: CHO replenishment and supplementation is beneficial for moderating post-strength training damage.